The dynamic hypoosmotic response of Vibrio cholerae relies on the mechanosensitive channel MscS - Kristen Ramsey; Madolyn Britt; Joseph Maramba; Blake Ushijima; Elissa Moller; Andriy Anishkin; Claudia Häse; Sergei Sukharev (iScience, 2024)
Summary: Vibrio cholerae adapts to osmotic down-shifts by releasing metabolites through two mechanosensitive (MS) channels, low-threshold MscS and high-threshold MscL. To investigate each channel’s contribution to the osmotic response, we generated ΔmscS, ΔmscL, and double ΔmscL ΔmscS mutants in V. cholerae O395. We characterized their tension-dependent activation in patch-clamp, and the millisecond-scale osmolyte release kinetics using a stopped-flow light scattering technique. We additionally generated numerical models describing osmolyte and water fluxes. We illustrate the sequence of events and define the parameters that characterize discrete phases of the osmotic response. Survival is correlated to the extent of cell swelling, the rate of osmolyte release, and the completeness of post-shock membrane resealing. Not only do the two channels interact functionally, but there is also an up-regulation of MscS in the ΔmscL strain, suggesting transcriptional crosstalk. The data reveal the role of MscS in the termination of the osmotic permeability response in V. cholerae.